The Role of Human Resource Management in The Succession Planning Process - Hudiyah, Dewi; Sutarto, Bambang; Marthalia, Lia; Prayudo, Gito; Prihatini, Prihatini (Research Horizon, 2025)
Organizations experience leadership deficits without succession planning, which can potentially lead to operational disruption and strategic failure. This study aims to uncover the contribution of Human Resource Management in Succession Planning, as well as identify the tactics and strategies implemented to support Leader Development. This study applies the Systematic Literature Review method to review articles on Human Resource Management and succession planning published between 2001 and 2024. The research process consists of identification, selection, evaluation, and integration, resulting in 11 related articles that provide a solid foundation for analysis and discussion. Based on the literature analysis conducted on 11 selected journals, which were further analyzed using thematic analysis method. The research findings indicate that active participation of HRM in Succession Planning not only strengthens Leader Development but also supports increased employee engagement and organizational culture. The implications of this study emphasize the need to incorporate HRM strategies in Succession Planning as a step to ensure leadership sustainability and improve overall organizational performance.